Validation of the Benefits of Ambulation Within 8 Hours of Elective Cervical and Lumbar Surgery: A Michigan Spine Surgery Improvement Collaborative Study. Issue 3 (17th September 2022) - Lim, Seokchun; Bazydlo, Michael; Macki, Mohamed; Haider, Sameah; Hamilton, Travis; Hunt, Rachel; Chaker, Anisse; Kantak, Pranish; Schultz, Lonni; Nerenz, David; Schwalb, Jason M.; Abdulhak, Muwaffak; et al.
Abstract : BACKGROUND: Early ambulation is considered a key element to Enhanced Recovery After Surgery protocol after spine surgery. OBJECTIVE: To investigate whether ambulation less than 8 hours after elective spine surgery is associated with improved outcome. METHODS: The Michigan Spine Surgery Improvement Collaborative database was queried to track all elective cervical and lumbar spine surgery between July 2018 and April 2021. In total, 7647 cervical and 17 616 lumbar cases were divided into 3 cohorts based on time to ambulate after surgery: (1) <8 hours, (2) 8 to 24 hours, and (3) >24 hours. RESULTS: For cervical cases, patients who ambulated 8 to 24 hours (adjusted odds ratio [aOR] 1.38; 95% CI 1.11-1.70; P = .003) and >24 hours (aOR 2.20; 95% CI 1.20-4.03; P = .011) after surgery had higher complication rate than those who ambulated within 8 hours of surgery. Similar findings were noted for lumbar cases with patients who ambulated 8 to 24 hours (aOR 1.31; 95% CI 1.12-1.54; P < .001) and >24 hours (aOR 1.96; 95% CI 1.50-2.56; P < .001) after surgery having significantly higher complication rate than those ambulated <8 hours after surgery. Analysis of secondary outcomes for cervical cases demonstrated that <8-hour ambulation was associated with home discharge, shorter hospital stay, lower 90-day readmission, and lower urinary retention rate. For lumbar cases, <8-hour ambulation was associated with shorter hospital stay, satisfaction with surgery, lower 30-day readmission, home discharge, and lower urinary retention rate. CONCLUSION: Ambulation within 8 hours after surgery is associated with significant improved outcome after elective cervical and lumbar spine surgery.